Polaronic Trions at the MoS2/SrTiO3 Interface. Issue 41 (26th August 2019) - Sarkar, Soumya; Goswami, Sreetosh; Trushin, Maxim; Saha, Surajit; Panahandeh‐Fard, Majid; Prakash, Saurav; Tan, Sherman Jun Rong; Scott, Mary; Loh, Kian Ping; Adam, Shaffique; Mathew, Sinu; Venkatesan, Thirumalai
Abstract: The reduced electrical screening in 2D materials provides an ideal platform for realization of exotic quasiparticles, that are robust and whose functionalities can be exploited for future electronic, optoelectronic, and valleytronic applications. Recent examples include an interlayer exciton, where an electron from one layer binds with a hole from another, and a Holstein polaron, formed by an electron dressed by a sea of phonons. Here, a new quasiparticle is reported, "polaronic trion" in a heterostructure of MoS2 /SrTiO3 (STO). This emerges as the Fröhlich bound state of the trion in the atomically thin monolayer of MoS2 and the very unique low energy soft phonon mode (≤7 meV, which is temperature and field tunable) in the quantum paraelectric substrate STO, arising below its structural antiferrodistortive (AFD) phase transition temperature. This dressing of the trion with soft phonons manifests in an anomalous temperature dependence of photoluminescence emission leading to a huge enhancement of the trion binding energy (≈70 meV). The soft phonons in STO are sensitive to electric field, which enables field control of the interfacial trion–phonon coupling and resultant polaronic trion binding energy. Polaronic trions could provide a platform to realize quasiparticle‐based tunable optoelectronic applications driven by many body effects. Abstract : A strong interfacial coupling between the trions in 2D MoS2 and soft phonons emerging below the antiferrodistortive phase transition in SrTiO3 gives rise to a new quasiparticle, the "Polaronic Trion." The polaronic trion has a very high binding energy that is electric field tunable, significant for trion‐based low‐loss optoelectronic devices.